Solving close-coupling equations in momentum space without singularities for charged targets - Bray, A.; Abdurakhmanov, I.; Kadyrov, A.; Fursa, D.; Bray, Igor (Elsevier BV, 2017)
The analytical treatment of the Green's function in the convergent close-coupling method (Bray et al., 2016) has been extended to charged targets. Furthermore, we show that this approach allows for calculation of cross sections at zero channel energy. For neutral targets this means the electron scattering length may be obtained from a single calculation with zero incident energy. For charged targets the non-zero excitation cross sections at thresholds can also be calculated by simply setting the incident energy to the exact threshold value. These features are demonstrated by considering electron scattering on H and He+.